From Governance to Identity
XIII, 162 p.
Keywords: On the occasion of Mary Henkel’s seventieth birthday a group of her colleagues have come together to write this volume of articles as a tribute to her work and a token of gratitude for contributions to higher education research. The authors analyse these developments leading up to and possibly beyond the present in a tribute to Mary Henkel’s work using her birthday as an occasion to focus attention on her contributions to higher education research – something she would normally seek to avoid. This book is also a contribute to understanding how research in higher education has developed since its origins as Mary Henkel was one of its founding scholars together with other well-known researchers such as Maurice Kogan, Guy Neave, Ulrich Teichler, Martin Trow, Burton Clark, etc. The book will be useful to all researchers in areas related to higher education, namely governance, academic work, academic identities and quality.